A comparative evaluation of the marginal accuracy of crowns fabricated from four commercially available provisional materials: An in vitrostudy - Bhavya Mohandas Amin; Meena Ajay Aras; Vidya Chitre (Wolters Kluwer Medknow Publications, 2015)
Purpose: The purpose of this in vitro study was to evaluate and compare the primary marginal accuracy of four commercially available provisional materials (Protemp 4, Luxatemp Star, Visalys Temp and DPI tooth moulding powder and liquid) at 2 time intervals (10 and 30 min). Materials and Methods: A customized stainless steel master model containing two interchangeable dies was used for fabrication of provisional crowns. Forty crowns (n = 10) were fabricated, and each crown was evaluated under a stereomicroscope. Vertical marginal discrepancies were noted and compared at 10 min since the start of mixing and then at 30 min. Observations and Results: Protemp 4 showed the least vertical marginal discrepancy (71.59 μ), followed by Luxatemp Star (91.93 μ) at 10 min. DPI showed a marginal discrepancy of 95.94 μ while Visalys Temp crowns had vertical marginal discrepancy of 106.81 μ. There was a significant difference in the marginal discrepancy values of Protemp 4 and Visalys Temp. At 30 min, there was a significant difference between the marginal discrepancy of Protemp 4 crowns (83.11 μ) and Visalys Temp crowns (128.97 μ) and between Protemp 4 and DPI (118.88 μ). No significant differences were observed between Protemp 4 and Luxatemp Star. Conclusion: The vertical marginal discrepancy of temporary crowns fabricated from the four commercially available provisional materials ranged from 71 to 106 μ immediately after fabrication (at 10 min from the start of mix) to 83-128 μ (30 min from the start of mix). The time elapsed after mixing had a significant influence on the marginal accuracy of the crowns.